The Ponseti Technique for the Treatment of Congenital Club foot at OPD in Rajshahi Medical College Hospital - Sohel, DM; Iqbal, A Asif; Dutta, P; Dam, BK; Ahmed, S; Yasmin, T (TAJ: Journal of Teachers Association, 2011)
Congenital club foot is the most common congenital deformity of the foot. Its characteristics presentation of equinus, varus, adductus and cavus deformities makes it easily recognizable. The estimated ratio is 1 or 2 per 1000 live births.It is a complex deformity that is difficult to correct. The goal when treating idiopathic clubfoot is achieve a foot with appearance and function that are nearly normal. There various types of treatment options for correction of the foot. (1) conservative, (2) surgery. The most frequently used surgical approach is posterio medial release which has many variation. However, long term follow up studies showed that the results of surgical treatment are disappointing. Ignacio Ponseti MD is the man who changed the previous treatment plan of club foot. Ponseti developed his method of club foot manipulation based on his understanding of normal anatomy of subtalar joint. In OPD of Rajshahi Medical College Hospital we studied 262 patients with congenital club foot, in which 188 were male and 74 were female. Total number of tenotomy undertaken 172, patients using braces 200. In our short term follow up our result is encouraging. TAJ 2011; 24(1): 26-29